IMPLEMENTASI METODE TEAM QUIZ PADA PEMBELAJARAN FIKIH PUASA DI SALAH SATU SEKOLAH DASAR - Annisa Nurdianti; Fadilah Prabowo; Muslim (STIT Hidayatunnajah Bekasi, 2022)
This study examines the use of the Team Quiz method to improve Fasting Fiqh learning in an elementary school in Karawang. The problem addressed is the use of monotonous teaching methods that reduce student interest and engagement. Using a qualitative case study approach, data were collected through observation, interviews, and documentation. The findings show that the Team Quiz method increases student participation, improves practice scores, and creates a more enjoyable learning atmosphere. However, challenges include dominant participation by high-achieving students and the need for strong teacher supervision. Overall, the method is effective in enhancing students’ understanding and involvement, with positive responses as it helps reinforce comprehension and memory